A dual cohesin-dockerin complex binding mode in Bacteroides cellulosolvens contributes to the size and complexity of its cellulosome - Duarte, Marlene (2021)
The Cellulosome is an intricate macromolecular protein complex that centralizes the cellulolytic efforts of many anaerobic microorganisms through the promotion of enzyme synergy and protein stability. The assembly of numerous carbohydrate processing enzymes into a macromolecular multiprotein structure results from the interaction of enzyme-borne dockerin modules with repeated cohesin modules present in noncatalytic scaffold proteins, termed scaffoldins. Cohesin- dockerin (Coh-Doc) modules are typically classified into different types, depending on structural conformation and cellulosome role. Thus, type I Coh-Doc complexes are usually responsible for enzyme integration into the cellulosome, while type II Coh-Doc complexes tether the cellulosome to the bacterial wall. In contrast to other known cellulosomes, cohesin types from Bacteroides cellulosolvens, a cellulosome-producing bacterium capable of utilizing cellulose and cellobiose as carbon sources, are reversed for all scaffoldins, i.e., the type II cohesins are located on the enzyme-integrating primary scaffoldin, whereas the type I cohesins are located on the anchoring scaffoldins. It has been previously shown that type I B. cellulosolvens interactions possess a dual-binding mode that adds flexibility to scaffoldin assembly. Herein, we report the structural mechanism of enzyme recruitment into B. cellulosolvens cellulosome and the identification of the molecular determinants of its type II cohesin-dockerin interactions. The results indicate that, unlike other type II complexes, these possess a dual-binding mode of interaction, akin to type I complexes. Therefore, the plasticity of dualbinding mode interactions seems to play a pivotal role in the assembly of B. cellulosolvens cellulosome, which is consistent with its unmatched complexity and size.